(untitled) (Journal of the Medical College for Women & Hospital, 2025)
Background: Platelet count is altered with alteration of body iron status. Both thrombocytosis and thrombocytopenia have been observed in iron deficiency anemia. Iron deficiency anemia is a common form of nutritional anemia in Bangladesh. Changes in platelet count in iron depleted conditions may increase the future risk of thromboembolic complications. Materials and Method: This cross-sectional study was conducted to assess platelet count in relation to iron status in adult population of Dhaka city. A total number of 108 study subjects of both sexes (40 male and 68 female) aged 18 – 45 years were selected. Study subjects were grouped into three groups on the basis of hemoglobin (Hb) concentration. In group A (Hb. 8 – 10.9 gm/dl), 31 study subjects were included. In group B (Hb. 11- 11.9 gm/dl), 34 study subjects were included and in group C (Hb. ≥12 gm/dl), 43 study subjects were included. Hematological parameters (hemoglobin concentration, platelet count) were measured by the automated hematology analyzer and iron parameters (serum iron, serum ferritin, total iron binding capacity) were measured by automated biochemistry analyzer in the Department of Laboratory Medicine, Dhaka Medical College, Dhaka. For statistical analysis one way ANOVA followed by Bonferroni test and Pearson’s correlation coefficient (r) test were performed as applicable using SPSS for Windows version 25. Results: In this study, serum iron showed statistically significant negative correlation with platelet count (r= -0.645, p <0.001) and serum ferritin showed statistically significant negative correlation with platelet count (r= -0.572, p <0.001) and total iron binding capacity showed statistically significant positive correlation with platelet count (r= 0.555, p <0.001). Conclusion: This study concluded that lower serum iron, serum ferritin and higher total iron binding capacity cause increase in platelet count. The changes in platelet count negatively correlated with iron status and positively correlated with severity of iron deficiency anemia. J Med Coll Women Hosp.2025; 21 (1):75-85